How should professional psychiatric associations respond to a large-scale disaster? - Emre Mutlu; Alper Bülbül; Emre Cem Esen; İrem Ekmekçi Ertek; H. Rengin Güvenç; Koray Başar; M. Hamid Boztaş; M. İrem Yıldız; Münevver Hacıoğlu Yıldırım; Rümeysa Taşdelen; Ejder Akgün Yıldırım (European Psychiatry)
Disasters pose unique challenges, triggering significant psychological and social crises with both short- and long-term impacts. In this article, we address the critical role of professional psychiatric associations (PPAs) in responding to large-scale disasters, emphasizing the operational model connected with the Psychiatric Association of Türkiye’s (PAT) response to the 2023 earthquakes in Türkiye and Northern Syria. We propose the SOLIDARITE model, a structured response framework, which incorporates sustained preparedness, organized networks, resource libraries, on-site and remote interventions, and comprehensive disaster planning across early, middle, and long-term phases. The model emphasizes a multidimensional approach integrating pre-disaster preparedness through training, various psychosocial support options, the establishment of networks, and the formulation of a master disaster response plan. The implementation of this model by PAT during the 2023 earthquakes facilitated an effective and prompt response, underlining the importance of PPAs’ role in disaster preparedness and action. The SOLIDARITE model supports the need for deeper integration of disaster psychiatry into psychiatric training and calls for national and international collaboration to enhance the preparedness and response capacity of PPAs.